Circular RNA and Diabetes: Epigenetic Regulator with Diagnostic Role - Abbaszadeh-Goudarzi, Kazem; Radbakhsh, Shabnam; Pourhanifeh, Mohammad H.; Khanbabaei, Hashem; Davoodvandi, Amirhosein; Fathizadeh, Hadis; Sahebkar, Amirhossein; Shahrzad, Mohammad Karim; Mirzaei, Hamed (Current Molecular Medicine, 2020)
Circular RNAs, a group of endogenous non-coding RNAs, are characterized by covalently closed cyclic structures with no poly-adenylated tails. It has been recently recommended that cirRNAs have an essential role in regulating genes expression by functioning as a translational regulator, RNA binding protein sponge and microRNA sponge. Due to their close relation to the progression of various diseases such as diabetes, circRNAs have become a research hotspot. A number of circRNAs (i.e., circRNA_0054633, circHIPK3, circANKRD36, and circRNA11783-2) have been shown to be associated with initiation and progression of diabetes. Based on reports, in a tissue, some circRNAs are expressed in a developmental stage-specific manner. In this study, we reviewed research on circular RNAs involved in the pathogenesis and diagnosis of diabetes and their prognostic roles.
Keywords: diabetes